1995
DOI: 10.1038/bjc.1995.341
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in ovarian neoplasms

Abstract: Summary Microsatellite instability has been observed in a variety of sporadic malignancies, but its existence in sporadic ovarian cancer has been the subject of conflicting reports. We have performed a polymerase chain reaction-based microsatellite analysis of DNAs extracted from the neoplastic and non-neoplastic tissues of 41 ovarian cancer patients. Tumour-associated alterations were observed in seven (17%) of these cases. Clinicopathological correlations revealed that: (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 30 publications
5
55
1
1
Order By: Relevance
“…We found 12.5% of ovarian tumours showed hMLH1 hypermethylation, and a corresponding loss of hMLH1 expression, only slightly below the frequency (15%) at which the MIN+ phenotype is estimated to occur in sporadic ovarian cancer (Hatta et al, 1997;Fujita et al, 1995;King et al, 1995). Furthermore, we found that in all the tumours in which we did not detect promoter hypermethylation hMLH1 expression was high.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…We found 12.5% of ovarian tumours showed hMLH1 hypermethylation, and a corresponding loss of hMLH1 expression, only slightly below the frequency (15%) at which the MIN+ phenotype is estimated to occur in sporadic ovarian cancer (Hatta et al, 1997;Fujita et al, 1995;King et al, 1995). Furthermore, we found that in all the tumours in which we did not detect promoter hypermethylation hMLH1 expression was high.…”
Section: Discussioncontrasting
confidence: 62%
“…About 15% of sporadically occurring ovarian tumours show microsatellite instability (Hatta et al, 1997;Fujita et al, 1995;King et al, 1995), suggesting that there is a defect in mismatch repair in these tumours. To determine if methylation of the promoter region of hMLH1 could be a potential cause of mismatch repair defects in ovarian tumours, DNA was extracted from 24 ovarian tumour samples and used for Southern blot analysis.…”
Section: Methylation Status Of Hmlh1 In Ovarian Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the length of these sequences, either by expansion or contraction of the repeat motifs, are characteristic of hereditary non-polyposis colorectal cancer (HNPCC) and a proportion of sporadic carcinomas of the colon, breast, ovary, prostate, stomach, lung, bladder, endometrium and oesophagus (Aaltonen et al, 1993;Ionov et al, 1993;Patel et al, 1994;Thibodeau et al, 1993;King et al, 1995;Uchida et al, 1995;Han et al, 1993;Merlo et al, 1994;Gonzalez-Zulueta et al, 1993;Risinger et al, 1993;Meltzer et al, 1994).…”
mentioning
confidence: 99%
“…Allelotyping studies have identified common sites of LOH on chromosomes 5q, 6q, 11p, 13q, 14q, 15q, 18q, Xp (Cliby et al, 1993;Osborne and Leech, 1994), and particularly on chromosome 7q (Zenklusen et al, 1995), 9q (Schultz et al, 1995) and 17p (Phillips et al, 1993). The occurrence of novel alleles at microsatellite loci, due to either a replication error phenotype (RER + ) resulting from defective mismatch repair or general genetic instability, has been described in 17-37% of ovarian tumours (Fujita et al, 1995;King et al, 1995;Sood and Buller, 1996). However, MI may occur in up to 75% of stage I ovarian tumours, and 71% of uncommon histopathological types such as endometrioid or mixed serous and mucinous tumours (King et al, 1995).…”
mentioning
confidence: 99%